Accurate metabolic images of the human myocardium by means of 31P magnetic resonance chemical shift imaging with spatial saturation pulses. (September 2013) - Geier, Oliver; Weng, Andreas Max; Ruff, Jan; Machann, Wolfram; Horn, Michael; Hahn, Dietbert; Spindler, Matthias; Beer, Meinrad; Köstler, Herbert
<x xml:space="preserve">Abstract</x> The aim of this study was to demonstrate that acquisition‐weighted 31P magnetic resonance spectroscopy with spatial saturation allows for generation of metabolite maps showing the distribution of 31P metabolites, such as phosphocreatine (PCr) and adenosine triphosphate (ATP) in the human myocardium. The method presented here allowed for a considerable shortening of the normally complicated and time‐consuming post‐processing. All examinations were performed on a 1.5 T scanner. Contamination from adjacent organs to the myocardial signal was suppressed using spatial saturation pulses and an acquisition‐weighted sampling scheme. All measurements were ECG‐triggered and performed in prone position. Both healthy subjects and patients with infarcted myocardium were examined. For comparison of the spectroscopic findings to a conventional technique, the infarcted myocardium was additionally examined with a late‐enhancement technique. The distribution of PCr of the whole left ventricular myocardium could be determined both in healthy subjects and in patients. The measured distribution of PCr in the infarcted myocardium revealed an obvious reduction of signal in the infarcted area, whereas the distributions of the metabolites in healthy myocardium reflected no discontinuities. The study could demonstrate that the application of spatial saturation pulses facilitates the visual representation of 31P metabolites with a post‐processing procedure easy to apply. © 2014 Wiley Periodicals, Inc. Concepts Magn Reson Part A 42A: 187–195, 2013.